Formação básica em engenharia: a articulação das disciplinas pelo cálculo diferencial e integral - Santos, Janice Valia de Los (2009)
The present research aimed at studying the articulation of the basic formation subjects of the Engineering courses through the Differential and Integral Calculus. Thus, in this study, it was proposed a methodology which could guide the calculus activities and could be constituted as integrative experiences in the course. In order to accomplish the goals, it was also necessary to study the teachers role so as the learning process could be built. For this reason, a field research with the Differential and Integral Calculus subject, which is part of the basic formation of the Engineering course of Cruzeiro do Sul University, was developed. After accomplishing the activities, it was noticed that using integrative activities such as the ones suggested in the research by the proposed methodology is viable for the results showed the students have acquired scientific knowledge, have developed their creativity as well as basic concepts for problem solving in their specific formation